Mechanism of HJ11 Decoction in the Treatment of Atherosclerosis Based on Network Pharmacology and Experimental Validation - Lu, Fei; Zou, Jiaxi; Xu, Weiming; Zhang, Fangyuan; Nie, Wenyi; Zhao, Yue; Jiang, Lijie; Liang, Lizhe; Hu, Jingqing (Combinatorial Chemistry & High Throughput Screening, 2025)
Background HJ11 (HJ11 decoction), which is based on the traditional prescription Si-Miao-Yong-An decoction, has exerted a remarkable effect on atherosclerosis (AS). Nevertheless, the main components and underlying mechanisms of HJ11 for treating AS remain unclear. Aim of the Study This study was designed to elucidate the mechanism of HJ11 in the treatment of AS through network pharmacology and in vivo experimental validation. Methods Network pharmacology was employed to explore the primary bioactive components and targets of HJ11. AS-related genes were obtained from the GeneCards and DisGeNET databases and screened for intersections with HJ11. A herb-compound-target interaction network was constructed by Cytoscape 3.9.1, and molecular docking analyses were constructed on key targets. By using a mouse model, the mechanism of action of HJ11 was further confirmed. Results A total of 231 active components of HJ11, 1681 AS-related genes, and 156 common targets were identified. Through the establishment of numerous networks, it was discovered that the main association of the mechanism of HJ11 in AS therapy pertained to anti-inflammation. Important substances included quercetin, kaempferol, and luteolin, while TNF-α, AKT1, IL-6, and VEGFA were the main targets. Molecular docking demonstrated that there were favorable binding interactions between active drugs (quercetin, kaempferol, and luteolin) and targets (TNF-α, AKT1, IL-6, and VEGFA). In the in vivo study, HJ11 reduced the expression of TNF-α, AKT1, IL-6, and VEGFA at both the mRNA and protein levels, inhibited atherosclerotic lesions in AS mouse models, and retarded the development of retroarterioid sclerosis. Conclusion HJ11 can inhibit inflammation and the progression of AS, and the mechanism might involve downregulating the expression of TNF-α, AKT1, IL-6, and VEGFA.
Keywords: network pharmacology